1993
DOI: 10.1113/jphysiol.1993.sp019969
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical determinants of gradient walking energetics in man.

Abstract: SUMMARY1. The metabolic cost and the mechanical work at different speeds during uphill, level and downhill walking have been measured in four subjects.2. The mechanical work has been partitioned into the internal work (JWiit), due to the speed changes of body segment with respect to the body centre of mass (BCM), and the external work (WJxt), related to the position and speed changes of the BCM in the environment.3. Wext has been further divided into a positive part (W,+xt) and a negative one (Wj-xt), associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
186
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(208 citation statements)
references
References 18 publications
(17 reference statements)
17
186
5
Order By: Relevance
“…As mentioned earlier, the trajectory of the centre of mass is monotonically ascending (or descending) at that steepness (Minetti et al 1993). Thus, potential energy change is the predominant component of the external work and is likely to be the same in both groups.…”
Section: K1mentioning
confidence: 73%
See 1 more Smart Citation
“…As mentioned earlier, the trajectory of the centre of mass is monotonically ascending (or descending) at that steepness (Minetti et al 1993). Thus, potential energy change is the predominant component of the external work and is likely to be the same in both groups.…”
Section: K1mentioning
confidence: 73%
“…Five porters and five Caucasians (71.2G11.1 kg, 1.73G0.05 m, 31.2G5.8 years, four of which were professional/expert mountaineers) were asked to ascend and descend 22% steep paths (482 and 325 m long, respectively, in the two locations) loaded with 25, 45 and 60 kg in their doko/rucksack, at a speed they could maintain for several hours. The paths were chosen in order to make sure that the trajectory of the body centre of mass was monotonically increasing or decreasing and no pendulum-like strategy could be adopted within the step (Minetti et al 1993). In this way, the mechanical power is prevalently determined by the rate of change of potential energy (see §1).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that the metabolic cost of eccentric muscle actions is much less than that of concentric contractions (Asmussen 1953;BiglandRitchie and Woods 1976;Rall 1985). As Minetti et al (1993) showed, a change in the relative contribution of concentric and eccentric muscle actions, combined with the difference in metabolic costs between both muscle actions will lead to very small increases in the metabolic cost for running up shallow inclines. Consequently, for running up shallow inclines, as used in the present study, the D efficiency will be much greater than the concentric muscle efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Surface compliance and damping can affect locomotion energetics and dynamics (Ferris et al, 1998;Ferris et al, 1999;Kerdok et al, 2002), as do surface inclines or declines (Margaria, 1976;Minetti et al, 1993). However, few studies have characterized the biomechanics and energetics of walking on uneven surfaces.…”
Section: Discussionmentioning
confidence: 99%